Modified Copper for Reducing CO and HC Vehicle Exhaust Gas Emissions - Suhartoyo, Suhartoyo; Kristiawan, Y. Yulianto; Karminto, Karminto; Nugroho, Arif Setyo (Applied mechanics and materials, 2023)
This study aims to determine the effect of installing modified copper C-SiO2-ZSM5 in the exhaust, installing modified copper in the exhaust to reduce CO and HC. The two methods used to reduce CO and HC exhaust emissions are as follows: the first method is by mixing fossil fuels with ethanol. The fuel used is a mixture of gasoline + ethanol with variations of gasoline, E10, and E20. The second method is to provide a CO and HC reformer catalyst made of modified copper with the addition of SiO2 and MZM5 as much as 10% and 20%, respectively. The test uses a four-stroke two-wheel motor in a neutral gear position. Exhaust emission data retrieval is at 1500, 3000, 5000, 7000, 9000 rpm. With gasoline fuel mixed with ethanol with E 10 and E 20. There is a decrease in CO at each engine speed in each fuel variation, because the more ethanol content, the greater the supply of O2 in combustion because ethanol has oxygen bonds that can increase combustion. The emission of CO and HC gas on gasoline-fueled motors are greater than those of E 10 and E 20 motors. The use of a copper converter catalyst SiO2-C-ZSM5 is very significant and can reduce CO levels for gasoline fuel from the highest value of 4,7% to 2.82%, gasohol fuel E 10 with the highest value of CO 3.02% decreased to 1.2% and gasohol fuel E 20 the highest value of CO 2.78% decreased to 0.17%. Changes were seen visually on the surface of the copper used for the CO and HC reduction test, the surface copper became darker in color, especially when testing using gasoline. When using a mixture of ethanol and gasoline, copper is purplish brown color.